2017
DOI: 10.1373/clinchem.2016.258780
|View full text |Cite
|
Sign up to set email alerts
|

When Gender Identity Doesn't Equal Sex Recorded at Birth: The Role of the Laboratory in Providing Effective Healthcare to the Transgender Community

Abstract: Understanding gender incongruence, the clinical changes associated with gender transition, and systemic barriers that maintain a gender/sex binary are key to providing adequate healthcare to transgender community. Transgender appropriate reference interval studies are virtually absent within the medical literature and should be explored. The laboratory has an important role in improving the physiological understanding, electronic medical system recognition, and overall social awareness of the transgender commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 53 publications
0
47
0
2
Order By: Relevance
“…Additionally, laboratory tests should be ordered based on biological sex (eg, prostate specific antigen [PSA] for transgender female, human chorionic gonadotropin [hCG] for transgender male). 39,45 For transgender patients who receive hormones and/or testosterone blockers, alterations in laboratory values may be present that are related to the pharmacology of the replacement therapies. Hormone replacement therapies can influence many hematologic, general chemistry, and special chemistry/endocrine values (Table 5).…”
Section: Preoperative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, laboratory tests should be ordered based on biological sex (eg, prostate specific antigen [PSA] for transgender female, human chorionic gonadotropin [hCG] for transgender male). 39,45 For transgender patients who receive hormones and/or testosterone blockers, alterations in laboratory values may be present that are related to the pharmacology of the replacement therapies. Hormone replacement therapies can influence many hematologic, general chemistry, and special chemistry/endocrine values (Table 5).…”
Section: Preoperative Carementioning
confidence: 99%
“…Hormone replacement therapies can influence many hematologic, general chemistry, and special chemistry/endocrine values (Table 5). 45 These changes to laboratory results are highly variable in terms of an increase, decrease, or no change as cited by Goldstein et al 45 When interpreting values for transgender patients receiving hormones, it is important to consider the physiology behind each test and whether the male or female range is more appropriate. It has been suggested that transitioning transgender patients on hormone replacement therapy for >6 months should have their laboratory values compared to that of their cis-counterparts and not their sex assigned at birth 45 However, limited evidence is available to guide the evaluation of laboratory test interpretation in the different stages of transition.…”
Section: Preoperative Carementioning
confidence: 99%
“…Unfortunately, the ways these values may change are not always consistent or predictable. Studies in adult populations have demonstrated a variety of findings, with the same laboratory values increasing, decreasing, or not significantly changing among different studies 34,35,39 (Table 4).…”
Section: Anesthesia and Perioperative Issuesmentioning
confidence: 99%
“…Other areas of pathology are also impacted by sex/gender incongruence . For example, receiving orders for pregnancy testing on male patients can lead to cancellation within some laboratory information systems.…”
mentioning
confidence: 99%
“…Other areas of pathology are also impacted by sex/ gender incongruence. 8 For example, receiving orders for pregnancy testing on male patients can lead to cancellation within some laboratory information systems. Additionally, tissue biopsies received from sex-specific anatomic locations, such as the cervix or prostate, may cause confusion when the tissue is logged into electronic systems.…”
mentioning
confidence: 99%